PENGARUH PUPUK BIOLAN 2 TERHADAP HASIL KACANG PANJANG (Vigna sinensis L.) - Rusnaini, Rusnaini (Universitas Muhammadiyah Palembang, 2017)
The experiment was conducted in Talang Inuman Teratai Urban Village, Muara Bulian Sub-District, Batang Hari Jambi Regency, with a height of 12 meters above sea level. The study aims to obtain Biolan 2 with the best dose that gives results in long bean plants. The experimental design used was Randomized Block Design (RAK) with six treatments consisting of N0: 0 liter /ha without fertilizer application Biolan 2, N1: 2 liters / ha of Biolan 2 fertilizer, N2: 4 liters / ha of Biolan 2 fertilizer, N3: 6 Liters / ha of Biolan 2 fertilizer, N4: 8 liters / ha of Biolan 2 fertilizer and N5: 10 liters / ha of Biolan 2 fertilizer. Each treatment was repeated four times with so many plot experiments 24 plots. For observations randomly taken 3 plants plot as sample. The observed components include pod length, number of pods, weight of pod and yield / ha. From the result of the research, Biolan 2 with dose 6 liters / ha has significant effect on the number of pods, weight of pod and yield per hectare but no effect on the administration of Biolan 2 with a dose of 8 liters / ha which gives the highest pod length.